Study Of The Potential Use Of The Hospital Without Walls Concept In Internal Medicine Health Services In The Outpatient Installation Of Mala Regional General Hospital, Talaud Regency - Yundi Y. Y. Tangkuman; Jimmy Posangi; Jeanette IC IC Manoppo (CV. Inara, 2025)
Introduction: The Hospital Without Walls (HWW) concept has become a strategic approach in the development of health services oriented towards efficiency and affordability, especially in challenging geographical areas such as Talaud Regency. HWW aims to expand the reach of hospital services beyond the physical boundaries of buildings by optimizing technology, cross-sector collaboration, and community participation. This study was motivated by the high number of visits of internal medicine patients to RSUD Mala without going through the referral mechanism from FKTP. This study aims to analyze the application of the HWW concept in internal medicine poly health services, analyze the application of the concept in reducing cold case rates, and identify obstacles and challenges that occur in its application at the RSUD Mala, Talaud Regency. Method: Huberman model. The research was conducted in March-July 2025 at RSUD Mala, Talaud Regency. Data collection techniques were carried out through in-depth interviews with five main informants, namely the hospital director, internal medicine specialist, family doctor, health center, doctor, and patient. Data was also strengthened by observation and documentation as an effort to triangulate sources and methods. Results: The implementation of HWW in RSUD Mala has started partially but has not been systematic. The hospital has started to apply HWW principles such as remote consultation and digital communication, but does not yet have operational SOPs and HR support and management systems in place. Informants see great opportunities in the development of this concept. In the context of cold cases, HWW plays an important role in initial screening through cooperation between primary care facilities and hospitals, education, back-referral, and utilization of telemedicine. Internal barriers include the absence of SOPs, limited facilities, and lack of HR training. External barriers include the absence of BPJS financing regulations and the lack of public understanding of HWW. Conclusion: RSUD Mala has great potential to develop HWW-based services, but requires systemic intervention in terms of policy, human resources, hospital information system development, and public education. The implementation of HWW can improve service efficiency, reduce hospital burden, accelerate case handling, and improve patient satisfaction.